Population Genetics of the Black Citrus Aphid Aphis aurantii (Hemiptera, Aphididae) in China - Liu, Hong-Ling; Chen, Zhi-Teng; Liu, Chao; Wu, Xing-Long; Xiao, Ke-Jun; Pu, De-Qiang (Frontiers in Ecology and Evolution, 2021)
The black citrus aphid, Aphis aurantiiBoyer de Fonscolombe, 1841, is one of the most destructive pests in commercial tea plantations and gardens in China. In this study, we investigated the population genetic structure of A. aurantii based on the concatenated sequences of two mitochondrial genes, cytochrome c oxidase I (cox1) and cytochrome b (cytb). A total of 166 haplotypes were identified from 177 individuals collected at 11 locations in China. The whole Chinese A. aurantii population showed a low nucleotide diversity (0.00968) and a high population diversity (haplotype diversity; 0.9991). The haplotypes of the 11 local populations were widely distributed in the neighbor-joining phylogenetic tree and haplotype network diagram, whereas no apparent lineages were detected. Gene flow analysis showed gene exchanges among local populations. The pairwise Fst values revealed a certain amount of genetic difference among local populations. Analysis of molecular variance (AMOVA) reflected genetic differences both within and among populations. The isolation by distance (IBD) analysis revealed a high positive correlation between the geographic distance and genetic distance of the different populations. Neutral test and mismatch distribution suggested that A. aurantii may have experienced recent population expansion events.